Dietary consumption as a risk factor for chronic non-communicable diseases in adolescents from Imbabura and Carchi 2019 (Horizontes de Enfermería, 2020)
The aim of this research was to identify dietary intake as a risk factor for chronic non-communicable diseases in adolescents from Imbabura and Carchi. It was a quali-quantitative, descriptive, cross-sectional study; the study population was constituted by 420 adolescents aged 10 to 18 years, who decided to participate in the research through a consent signed by the parents. The techniques used were: a family history survey on CNCD and a food consumption survey; the data were processed in Epi Info 7. The main results found were: frequent consumption of highly energetic preparations, added salt, sugars, sugary drinks, sweets and salt, and processed foods, and a large number of adolescents with a family history of CNCD. Conclusions: The frequency of dietary consumption of highly energetic foods was identified as a risk factor for CNCD, which can translate into ignorance of healthy eating.
Keywords: risk factor; CNCD; adolescents; food intake